Age-Related Effects of Inhalational Anesthetics in B4galnt1-Null and Cuprizone-Treated Mice: Clinically Relevant Insights into Demyelinating Diseases - Ozana Katarina Tot; Stefan Mrđenović; Vedrana Ivić; Robert Rončević; Jakov Milić; Barbara Viljetić; Marija Heffer (Current Issues in Molecular Biology, 2024)
Anesthetics are essential agents that are frequently used in clinical practice to induce a reversible loss of consciousness and sensation by depressing the central nervous system. The inhalational anesthetics isoflurane and sevoflurane are preferred due to their rapid induction and recovery times and ease of administration. Despite their widespread use, the exact molecular mechanisms by which these anesthetics induce anesthesia are not yet fully understood. In this study, the age-dependent effects of inhalational anesthetics on two demyelination models were investigated: congenital (B4galnt1-null) and chemically induced (cuprizone). Various motor and cognitive tests were used to determine sensitivity to isoflurane and sevoflurane anesthesia. B4galnt1-null mice, which exhibit severe motor deficits due to defects in ganglioside synthesis, showed significant impairments in motor coordination and balance in all motor tests, which were exacerbated by both anesthetics. Cuprizone-treated mice, which mimic the demyelination in B4galnt1-null mice, also showed altered, age-dependent sensitivity to anesthesia. The study showed that older mice exhibited more pronounced deficits, with B4galnt1-null mice showing the greatest susceptibility to sevoflurane. These differential responses to anesthetics suggest that age and underlying myelin pathology significantly influence anesthetic effects.